2016
DOI: 10.18632/oncotarget.13633
|View full text |Cite
|
Sign up to set email alerts
|

Metformin therapy and the risk of colorectal adenoma in patients with type 2 diabetes: A meta-analysis

Abstract: BackgroundExisting data evaluating the impact of metformin on the colorectal adenoma (CRA) risk in patients suffering from type 2 diabetes (T2D) are limited and controversial. We therefore summarized the studies currently available and assessed the relationship between metformin treatment and risk of CRA in T2D patients.MethodsWe systematically searched databases for eligible studies that explored the impact of metformin treatment on the occurrence of CRA in T2D patients from inception to June 2016. The summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 73 publications
(98 reference statements)
0
11
0
1
Order By: Relevance
“…Metformin, a biguanide drug, is the first line clinical agent for type 2 diabetes mellitus (T2D) treatment ( 8 , 9 ). The pharmacological mechanism of metformin is to downregulate blood glucose levels to enhance insulin sensitivity in the liver and peripheral tissues (stimulating glucose uptake into muscles and/or increasing fatty acid oxidation in adipose tissue) by activation of adenosine monophosphate (AMP)-activated protein kinase (AMPK) signaling ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Metformin, a biguanide drug, is the first line clinical agent for type 2 diabetes mellitus (T2D) treatment ( 8 , 9 ). The pharmacological mechanism of metformin is to downregulate blood glucose levels to enhance insulin sensitivity in the liver and peripheral tissues (stimulating glucose uptake into muscles and/or increasing fatty acid oxidation in adipose tissue) by activation of adenosine monophosphate (AMP)-activated protein kinase (AMPK) signaling ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of the 156 articles, there was a mixture of study types; 76 were retrospective cohorts 5, 18-92 , 27 were case-control studies 93-119 , 15 were meta-analyses [120][121][122][123][124][125][126][127][128][129][130][131][132][133][134] , 15 were prospective cohorts [135][136][137][138][139][140][141][142][143][144][145][146][147][148][149] , 11 were systematic reviews with a meta-analysis [150][151][152][153][154][155][156][157][158][159][160] , seven were nested case-control [161][162][163][164][165][166][167] , two were randomized control studies…”
Section: Resultsmentioning
confidence: 99%
“…Insulin resistance is also considered to be an underlying cause for the correlation between obesity and CRC [25]. Indeed, it was demonstrated that the anti-hyperglycemic agent metformin is associated with a decreased incidence of CRC [26]. It is also possible that insufficient bowel preparation, which is potentially more common in DM due to associated autonomic neuropathy and other comorbidities, increases the risk of detection failure [27], although we excluded colonoscopies with inadequate preparation from our analysis.…”
Section: Discussionmentioning
confidence: 99%